The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1574-6968.2007.01036.x
|View full text |Cite
|
Sign up to set email alerts
|

The isolation, purification and biological activity of a novel antibacterial compound produced byPseudomonas stutzeri

Abstract: A novel compound designated zafrin [4beta-methyl-5, 6, 7, 8 tetrahydro-1 (4beta-H)-phenanthrenone] was isolated from a crude extract of a marine bacterium identified as Pseudomonas stutzeri. Zafrin showed strong antibacterial activity against both Gram-positive and Gram-negative bacteria. The compound was purified and its structure was elucidated by spectroscopic methods including 1H-nuclear magnetic resonance (NMR), 13C-NMR, 1D-NMR and 2D-NMR spectroscopy. It could be demonstrated that a purified solution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…CMG1030 has antimicrobial activity. This organism was originally identiWed as P. aeruginosa, but the strain identiWcation was revised to P. stutzeri CMG1030, which produces the novel antibacterial compound zafrin [76]. Subsequently, the authors elucidated the chemical structure of zafrin and studied its antibacterial mechanism.…”
Section: Bioactivities Of Pseudomonas Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…CMG1030 has antimicrobial activity. This organism was originally identiWed as P. aeruginosa, but the strain identiWcation was revised to P. stutzeri CMG1030, which produces the novel antibacterial compound zafrin [76]. Subsequently, the authors elucidated the chemical structure of zafrin and studied its antibacterial mechanism.…”
Section: Bioactivities Of Pseudomonas Metabolitesmentioning
confidence: 99%
“…Marine isolates of P. stutzeri have also been reported to live in the Black Sea (southwest) at 120-m depth [69], in a deep-sea hydrothermal vent in the Galapagos Rift [62] and in the Ariake Sea tideland, Japan [40]. Strains of this species can degrade naphthalene [11-13, 60, 61], oxidize thiosulfate [69], and sulfur [62], denitrify [40], and produce urea [73] and antibiotics [1,[75][76][77]. Amachi et al [3] also have isolated Pseudomonas strain SCT, a dissimilatory iodate-reducing bacterium closely related to P. stutzeri.…”
Section: Ecological Diversity Of Marine Pseudomonasmentioning
confidence: 99%
“…Isnansetyo et al [81] have isolated a novel compound, zafrin (4b-methyl-5,6,7,8-tetrahydro-1 (4b-H)-phenanthrenone), from Pseudomonas stutzeri strain, which was isolated from Gulf of Karachi, Pakistan. The bactericidal effect of Zafrin was more efficient than ampicillin, vancomycin or tetracycline against Bacillus subtilis., and bacterial membrane was the target of its bactericidal due to its amphiphilic nature, disruption of bacteria membrane like nisin or triton X-100 antibacterial agents [82]. Similarly, Al-Gendy et al [83] have also reported antibacterial compound, ayamycin, derived from secondary metabolites of Nocardia sp.…”
Section: Marine Secondary Metabolites As An Antimicrobial Agentmentioning
confidence: 99%
“…Zafrin does not target the bacterial cell wall and its pattern of lysis resembles that of compounds such as nisin (14.91 µM) and Triton X‐100, which disrupt the cell membrane. It was suggested that the mode of action of zafrin is via the disruption of the cytoplasmic membranes, since the molecule is amphiphilic (Uzair et al ., 2008).…”
Section: Antimicrobial Secondary Metabolitesmentioning
confidence: 99%